CircGNG4 Promotes the Progression of Prostate Cancer by Sponging miR-223 to Enhance EYA3/c-myc Expression - Xu, Shengxian; Lian, Zhenpeng; Zhang, Siyang; Xu, Yong; Zhang, Hongtuan (Frontiers in Cell and Developmental Biology, 2021)
The prognosis of prostate cancer is poor and the treatment of prostate cancer is extremely challenging, but the specific pathogenesis of prostate cancer is unclear. CircRNA is a non-coding RNA that interacts with miRNA and transcription factors to regulate gene expression. However, little is known about which circRNA are important in the pathogenesis of prostate cancer.CircGNG4 is up-regulated in prostate cancer tissues and cell lines. Knockdown of circGNG4 inhibits malignant behaviors of prostate cancer cell. Bioinformatics predicted that circGNG4 would interact with miR-223 targeting EYA3/c-myc mRNA. miR-223 inhibited the malignant behavior of prostate cancer cells, while EYA3/c-myc had the opposite effect. CircGNG4enhances the expression of EYA3/c-myc by sponging miR-223 to promote the growth of xenograft prostate cancer tumors in vivo and in vitro.In conclusion, the circGNG4-miR-223-EYA3/c-myc regulatory pathway promotes the malignant progression of prostate cancer. Our findings may provide potential new targets for the diagnosis or treatment of prostate cancer.